Effect of Dietary Supplementation of Ferrous Sulphate on the Blood Biochemical Attributes and Development of Digestive Organs of Turkey Poults - Sharma, A.; Bhattacharyya, A.; Shukla, P. K.; Yadav, B.; Singh, V. K. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted during February–April, 2020 in the Department of Poultry Science, Pandit Deen Dayal Upadhyaya Pashu Chikitsa Vigyan Vishwavidyalaya Evam Go-Anusandhan Sansthan, Mathura, Uttar Pradesh, India to assess the effect of dietary supplementation of ferrous sulphate on the blood biochemical attributes of turkey poults. Nighty six straight run day old turkey poults were placed into four treatment groups, each with three replicates and eight turkey poults in each replicate. The poults were kept in a system with deep litter. The experiment was carried out on turkey poults aged 0 to 8 weeks. In the experiment, (control) basal diet, supplemented with FeSO4 @ 80 mg kg-1 diet, supplemented with FeSO4 @ 120 mg kg-1 diet, and supplemented with FeSO4 @ 160 mg kg-1 diet were provided to the poults. Blood was collected at the end of the experiment. Length and weight of different digestive organs were measured separately at 8 weeks of age after sacrificing birds. Plasma was separated and stored in refrigerator (-20°C) until analyzed. The data obtained showed that there was no significant difference in plasma total proteins, uric acid, ALT, AST, ALP, plasma cholesterol, plasma HDL, SOD, ROS, LPO values and development of digestive organs among different treatment groups. Further studies can be done by assessing the effect on blood biochemicals and digestive organ development of poultry birds by supplementing organic Fe chelates.